Targeting Autophagy for Developing New Therapeutic Strategy in Intervertebral Disc Degeneration - Md Entaz Bahar; Jin Seok Hwang; Mahmoud Ahmed; Trang Huyen Lai; Trang Minh Pham; Omar Elashkar; Kazi-Marjahan Akter; Dong-Hee Kim; Jinsung Yang; Deok Ryong Kim (MDPI AG, 2022)
Intervertebral disc degeneration (IVDD) is a prevalent cause of low back pain. IVDD is characterized by abnormal expression of extracellular matrix components such as collagen and aggrecan. In addition, it results in dysfunctional growth, senescence, and death of intervertebral cells. The biological pathways involved in the development and progression of IVDD are not fully understood. Therefore, a better understanding of the molecular mechanisms underlying IVDD could aid in the development of strategies for prevention and treatment. Autophagy is a cellular process that removes damaged proteins and dysfunctional organelles, and its dysfunction is linked to a variety of diseases, including IVDD and osteoarthritis. In this review, we describe recent research findings on the role of autophagy in IVDD pathogenesis and highlight autophagy-targeting molecules which can be exploited to treat IVDD. Many studies exhibit that autophagy protects against and postpones disc degeneration. Further research is needed to determine whether autophagy is required for cell integrity in intervertebral discs and to establish autophagy as a viable therapeutic target for IVDD.